The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/rs10091367
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Algorithm to Retrieve Significant Wave Height from Sentinel-1 Synthetic Aperture Radar Imagery Collected under Cyclonic Conditions

Abstract: In this study, an empirical algorithm is proposed to retrieve significant wave height (SWH) from dual-polarization Sentinel-1 (S-1) synthetic aperture radar (SAR) imagery collected under cyclonic conditions. The retrieval scheme is based on the well-known CWAVE empirical function that is here updated to deal with multi-polarization S-1 SAR measurements collected using the interferometric wide (IW) and the Extra Wide-Swath (EW) imaging modes, under cyclonic conditions. First, a training dataset that consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
(61 reference statements)
1
18
0
Order By: Relevance
“…Data for new assessments could have been done every 6 days after that, providing four assessments over time before the the full analysis from optical images was available. Sentinel-1 data has also proved its use for weather-related parameters in relation to cyclones [15] as in the case of Idai in Beira.…”
Section: Introductionmentioning
confidence: 99%
“…Data for new assessments could have been done every 6 days after that, providing four assessments over time before the the full analysis from optical images was available. Sentinel-1 data has also proved its use for weather-related parameters in relation to cyclones [15] as in the case of Idai in Beira.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite data used for real-time wave observations include altimeter data [16] and synthetic aperture radar (SAR) data [17]. Spaceborne SARs, such as the Chinese Gaofen-3 SAR, feature a large swath width (>500 km) and fine spatial resolution (e.g., 150 m), thereby enabling high-resolution monitoring of typhoon winds [17][18][19] and waves [20][21][22][23] on large spatial scales. However, SAR data are only acquired on demand and are therefore unavailable for long-term studies.…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, GMF algorithms cannot be applied to wind retrieval. Cross-polarization NRCS is useful for retrieving wind speed (Fois et al, 2015) and significant wave height (Shao et al, 2018b) in cyclones. Fois et al (2015) reported that future ocean scatterometry will take advantage of the cross-polarization backscattering signal to observe strong winds.…”
Section: Introductionmentioning
confidence: 99%